THE ROLE OF SOCIAL SUPPORT IN REDUCING STRESS IN PRE-ADOLESCENT CHILDREN - Munizu, Musran; Mubarok, Ahmad Shofi; Patemah, Patemah (Jurnal Kajian Pendidikan dan Psikologi, 2024)
This research aims to explore the role of social support in reducing stress among pre-adolescent children, focusing on the contributions of family, peers, and schools. Utilizing a quantitative approach, data were collected through questionnaires administered to 200 pre-adolescent children aged 9 to 12 years. The findings reveal that social support from family significantly correlates with lower stress levels, emphasizing the importance of emotional backing from parents. Additionally, peer support was found to be crucial, as children with strong friendships demonstrated better-coping mechanisms in stressful situations. School support, characterized by teachers’ attentiveness and a positive school environment, also played a vital role in mitigating stress among children. Moreover, demographic factors such as socioeconomic status and gender influenced the extent of social support received, with children from lower socioeconomic backgrounds reporting less access to support networks. The study highlights the critical need for parents, educators, and policymakers to foster supportive environments that can enhance children's emotional resilience and well-being. These findings contribute to the existing literature on child development and stress management, offering practical recommendations for improving the mental health of pre-adolescent children.